Cross-Border Mergers and Acquisitions (CBMAs): A Review on Top Six ASEAN Country CBMA Players - Nurhazrina Mat Rahim; Ruhani Ali (Asian Academy of Management Journal of Accounting and Finance, 2016)
Cross-Border Mergers and Acquisitions (CBMAs) are one of the vehicles for Foreign Direct Investment (FDI) and remain a popular external growth strategies by firms worldwide. However, World Investment Report 2015 (UNCTAD, 2015) reports a slight decrease of 16% in global FDI for year 2014. Nevertheless, FDI inflow to emerging economies especially the Association of Southeast Asian Nations (ASEAN) member countries increase by 5%. With the intensity of CBMAs in ASEAN member countries, this paper reviews the six ASEAN member countries which actively involved in CBMAs from January 2002 to December 2014. Discussion is also centered on how the main research stream on CBMAs (antecedents, impact of CBMA and determinants of firm performance) relates to CBMA trends by ASEAN member countries. Corporate governance spillover hypothesis is anticipated to explain the CBMA motivations of the ASEAN firms and also the variation in ASEAN firms' performance following CBMAs.